Comparison of two contemporary rotary systems in a pre‐clinical student course setting. (4th July 2015) - Marending, M.; Biel, P.; Attin, T.; Zehnder, M.
Abstract: Aim: To assess two contemporary rotary instrumenting systems subjectively and objectively in a pre‐clinical student course setting. Methodology: Undergraduate dental students ( n  = 44) prepared mesiolingual canals of 3D‐printed mandibular molar replicas (RepliDens, Zurich, Switzerland). The HyFlex and BioRace rotary systems, both previously unknown to the students, were used according to the manufacturers' guidelines after a short theoretical introduction. For comparison, a first‐generation rotary system (ProFile .04), which the students knew from their previous education, was then used in a third RepliDens. Questionnaires were issued to note subjective experiences immediately after instrumentation. Objectively, time to instrument to size 40, .04 taper and shaping outcomes were analysed. Categorical data were compared using chi‐square and Fisher's exact tests, numerical data according to goodness of fit to the normal distribution, P  <   0.05. Results: Subjectively, the students liked the file size and sequence designation in the BioRace system significantly ( P  <   0.05) better than in the HyFlex counterpart, whilst they found better controllability with the HyFlex ( P  <   0.05), and reported no difference in cutting efficiency. They preferred both systems to the ProFile. Objectively, canal transportation was significantly less with the HyFlex (and the ProFile) systems compared to BioRace ( P  <   0.05). Both systems under investigation were statistically similar in terms of file fractures (nil), length control, and instrumentation time, which was considerably faster than with the ProFile control system. Conclusions: HyFlex and BioRace had perceived and quantifiable strengths and weaknesses. Both systems were equally liked by the students and preferred over the ProFile first‐generation rotary system.